Patient safety incidents in ambulatory care in Germany. (13th November 2019) - Geraedts, M; Krause, S; Schneider, M; Leinert, J; de Cruppé, W
Abstract: Background: In contrast to the inpatient sector, reliable data on the epidemiology and public health impact of patient safety incidents (PSI) are hardly found in the outpatient sector. Thus, this study focusses on the incidence of PSI; the distribution among the various specialist groups; the harmful consequences; the causes and how affected patients deal with PSI in Germany. Methods: We conducted a cross-sectional study using a newly developed computer-assisted-telephone-interview survey tool. Based on random telephone numbers, citizens >39 years were asked to report whether they had experienced a PSI in the last year or since their 40th birthday; whereby the PSI happened, what consequences the PSI had for them and if they reported the PSI back to their physician. We performed descriptive and multivariate analyses and extrapolated the results to the total population >39 years in Germany. Results: 10037 citizens were surveyed (response rate 13%): 8841 had an outpatient visit last year, of whom 1570 (18%) had experienced at least one PSI. In total, 2832 PSI were reported. General practitioners caused 43% of PSI. Among specialists (54%), most PSI were found among orthopedists (15%) and internists (9%) and arose in connection with anamnesis and clinical examination (61%) as well as drug prescriptions (15%). 72% of the PSI caused health related harm. The most frequent harm was a deterioration in health (23%) and persistent pain (22%). 54% of those affected described the harm as severe or very severe. 27% considered doctors' stress and lack of time or poor communication (18%) as causes for PSI. 32% of PSI were reported back to the treating physician. Discussion: Extrapolated to the total population >39 years in Germany (47.2 million), an incidence of 12 million PSI per year must be expected with around 6.6 million affected outpatients. Thus, PSI in the outpatient sector are of immense public health importance in Germany. Key messages: Patient safety incidents (PSI) often happen in the German outpatient sector. Outpatient PSI can also be accompanied by severe harm for patients.